1997
DOI: 10.1172/jci119709
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress activates extracellular signal-regulated kinases through Src and Ras in cultured cardiac myocytes of neonatal rats.

Abstract: A growing body of evidence has suggested that oxidative stress causes cardiac injuries during ischemia/reperfusion. Extracellular signal-regulated kinases (ERKs) have been reported to play pivotal roles in many aspects of cell functions and to be activated by oxidative stress in some types of cells. In this study, we examined oxidative stress-evoked signal transduction pathways leading to activation of ERKs in cultured cardiomyocytes of neonatal rats, and determined their role in oxidative stress-induced cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

35
426
5
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 655 publications
(467 citation statements)
references
References 64 publications
35
426
5
1
Order By: Relevance
“…ERK activation downstream of ROS has been shown to be mediated by different signaling pathways, including growth factor receptors (epidermal growth factor receptor, platelet-derived growth factor receptor), Ras and PKC (Guyton et al, 1996;Aikawa et al, 1997;Martindale and Holbrook, 2002;Lee et al, 2003). We observed that the pan-PKC inhibitor GF109203X suppressed ERK and p38 activation and apoptosis induced by 4HPR, suggesting that PKC may be an upstream regulator of ERK in our system.…”
Section: Hpr-induced Apoptosis In Hnscc Cellsmentioning
confidence: 54%
See 1 more Smart Citation
“…ERK activation downstream of ROS has been shown to be mediated by different signaling pathways, including growth factor receptors (epidermal growth factor receptor, platelet-derived growth factor receptor), Ras and PKC (Guyton et al, 1996;Aikawa et al, 1997;Martindale and Holbrook, 2002;Lee et al, 2003). We observed that the pan-PKC inhibitor GF109203X suppressed ERK and p38 activation and apoptosis induced by 4HPR, suggesting that PKC may be an upstream regulator of ERK in our system.…”
Section: Hpr-induced Apoptosis In Hnscc Cellsmentioning
confidence: 54%
“…The proapoptotic role of ERK in 4HPR-induced cell death is a novel finding that is somewhat unexpected because ERK has been associated with enhanced cell proliferation (Chang and Karin, 2001) and increased survival signal that counteracted proapoptotic effects mediated by JNK and/or p38 activation (Xia et al, 1995;Seidman et al, 2001;Carvalho et al, 2004;Yu et al, 2004). Furthermore, oxidative stress has been shown to activate ERK as a protective mechanism (Guyton et al, 1996;Aikawa et al, 1997;Bhatt et al, 2002). However, a proapoptotic role has been demonstrated for ERK in several studies with different stimuli, including anticancer drugs (Stanciu et al, 2000;Wang et al, 2000;Guise et al, 2001;Xiao and Singh, 2002;Lee et al, 2003;Zhang et al, 2003;Nguyen et al, 2004).…”
Section: Hpr-induced Apoptosis In Hnscc Cellsmentioning
confidence: 99%
“…In those studies, pharmacologic agents as well as molecular alterations resulting in reduced ERK activation were found to sensitize 3T3 cells to hydrogen peroxide, while molecular strategies leading to elevated ERK activation enhanced survival of cells treated with the oxidant. Subsequent studies from a number of laboratories confirmed these findings in other cell types and with other model agents (Aikawa et al, 1997;Wang et al, 1998;Peus and Pittelkow, 2001;Ikeyama et al, 2001). However, other studies using different model systems have produced findings to suggest that ERK activation can contribute to apoptosis in response to oxidant injury.…”
Section: Erk Pathwaymentioning
confidence: 84%
“…What determines whether ERK will act in a pro-apoptotic or anti-apoptotic fashion remains an important unanswered question, but the kinetics and duration of its activation may be important factors. For example, in situations where ERK activity enhances survival, activation occurs rapidly and is more transient (Guyton et al, 1996a,b;Aikawa et al, 1997;Ikeyama et al, 2000), in situations where it is apoptotic, activation tends to be delayed and sustained (Jimenez et al, 1997;Wang et al, 2000a).…”
Section: Erk Pathwaymentioning
confidence: 99%
“…ROS are able to induce cardiomyocyte apoptosis in vitro (Aikawa et al, 1997;von Harsdorf et al, 1999). Hydrogen peroxide can induce the translocation of Bax and Bad from cytosol to mitochondria (von Harsdorf et al, 1999).…”
Section: Central Role Of Ros In Cardiomyocyte Apoptosismentioning
confidence: 99%